Green Synthesis of Gelatin‐Lipid Nanocarriers Incorporating Berberis aristata Extract for Cancer Therapy; Physical Characterization, Pharmacological and Molecular Modeling Analysis. Issue 45 (1st December 2022) - Zaib, Sumera; Saeed Shah, Hamid; Usman, Faisal; Shahzadi, Kiran; Mazhar Asjad, Hafiz; Khan, Riffat; Dera, Ayed A.; Adel Pashameah, Rami; Alzahrani, Eman; Farouk, Abd‐ElAziem; Khan, Imtiaz
Abstract: Cancer remains strongly associated with morbidity and lethality posing a massive challenge to public health from decades. Thus, new interventions, effective and meaningful therapeutic approaches towards the treatment of cancer are urgently required. In this regard, nanotechnology offers an efficacious pharmacological application towards anticancer therapy. Therefore, the current study was aimed to develop Berberis aristata aqueous extract loaded gelatin lipid‐nanocarriers to explore their in vitro and in vivo antitumor properties. The extract loaded gelatin lipid nanoparticles were formulated by using double emulsion solvent evaporation method and physical characterization was performed using various techniques. Hydrodynamic diameter, zeta potential and polydispersity index (PDI) of GLN‐BA were observed as 322±7 nm, −31.49±4.85 mV and 0.397±0.102 mV, respectively. The extract was efficiently entrapped within the GLN (EE=79±11 %) and follow the diffusion type release mechanism. Moreover, transmission electron microscopy (TEM) demonstrated the spherical shaped smooth morphology of nanospheres. In vitro anticancer activity of GLN‐BA was performed by SRB assay and shown to demonstrate effective cytotoxicity (IC50 =4.73±2.95 μ g/mL) against MCF‐7 which was further quantitatively and qualitatively verified by flow cytometry, genotoxicity and DAPI staining. Induction of apoptotic bodies provides the evidence for apoptosis mediated cytotoxicity. Further, in vivo analysis on female mice was carried out to corroborate anticancer activity and was comparable to cisplatin. At 10 th day, the GLN‐BA (10 mg/kg) prominently reduced the tumor volume to 35±11 % in consistent with cisplatin (3 mg/kg) which exhibited 41±5 % reduction. Moreover, molecular modeling analysis substantiates the stable nanoformulation encapsulating the BA bioactive constituent. Taken together, current findings supported the therapeutic effectiveness of BA encapsulated gelatin lipid nanoparticles towards breast cancer suggesting the use of medicinal plant as a prototype to treat tumor. Abstract : The Figure depicts results of pharmacological testing (both in vitro and in vivo). In vitro SRB assay represents cell viability (%) and cell death (%) against human breast cancer cells (MCF‐7) representing the IC50 values for pure extract and GLN‐BA treated cells (left). In vivo antitumor assessment in an animal model (right)